Sistem Prediksi Pengadaan Bahan Bangunan Menggunakan Metode Single Exponential Smoothing pada Toko Jaya Indah Bangunan Tanjungpinan - Abdul Rahmad, Rahmad; Zulfachmi, Zulfachmi; Desi, Desi (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2024)
Abstract— Toko Jaya Indah Bangunan is one of the shops located in Tanjungpinang city and is engaged in selling and providing building materials. Toko Jaya Indah Bangunan is located at Jalan Gatot Subroto. In procuring building materials, Toko Jaya Indah Bangunan usually first checks the stock of goods in the warehouse and also sees what trend in the market for goods is currently booming. If you have found the goods to be held and the goods are currently booming, then Toko Jaya Indah Bangunan will procure the goods. The problem that arises in procuring goods like this is that sometimes the number of goods ordered does not match what is needed by the community, causing stockpiles of goods to accumulate in the warehouse and hindering Toko Jaya Indah Bangunan in ordering other goods. This can be overcome if the Toko Jaya Indah Bangunan has a system that is able to check the available stock of goods directly without having to check the warehouse first, and also determine the number of items held using a prediction system. The methodology used for the development of this application is the waterfall methodology, the reason is because this method has stages of application development that are in accordance with the way the author developed this application by going through the stages of analysis, design, coding, testing and application. And for the calculation method in making this prediction, the author uses the Single Exponential Smoothing method which this method uses reference data that has a fixed pattern. This prediction model was chosen because the data obtained contains a stationary pattern (tends to be fixed and does not change). From the results of the design, we get a system that is able to predict the exact amount of the purchase of an item made by Toko Jaya Indah Bangunan and this prediction system is made using the Java language, MySQL database and desktop-based. Keywords— Prediction, Purchase, Building Materials, Single Exponential Smoothing, Waterfall